2007
DOI: 10.1007/s12033-007-0044-y
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Amplification of Genomic DNA from Recalcitrant Dried Berries of Black Pepper (Piper nigrum L.)—A Medicinal Spice

Abstract: Black pepper is an important medicinal spice traded internationally. The extraction of high quality genomic DNA for PCR amplification from dried black pepper is challenging because of the presence of the exceptionally large amount of oxidized polyphenolic compounds, polysaccharides and other secondary metabolites. Here we report a modified hexadecyl trimethyl ammonium bromide (CTAB) protocol by incorporating potassium acetate and a final PEG precipitation step to isolate PCR amplifiable genomic DNA from dried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 12 publications
(14 reference statements)
0
10
0
Order By: Relevance
“…We found that the addition of 0.5 M glucose to the extraction buffer improved DNA quality, avoiding contamination and browning by polyphenolics as reported by Permingeati et al (1998). Using ammonium acetate in the extraction procedure could also be of great importance (Dhanya et al 2007). Increasing the extraction buffer volume from the usual 4 ml per gram of tissue to 6 ml resulted in an improved DNA yield.…”
Section: Resultsmentioning
confidence: 99%
“…We found that the addition of 0.5 M glucose to the extraction buffer improved DNA quality, avoiding contamination and browning by polyphenolics as reported by Permingeati et al (1998). Using ammonium acetate in the extraction procedure could also be of great importance (Dhanya et al 2007). Increasing the extraction buffer volume from the usual 4 ml per gram of tissue to 6 ml resulted in an improved DNA yield.…”
Section: Resultsmentioning
confidence: 99%
“…Oaks ( Quercus spp.) have been frequently reported to be some of the most challenging species to obtain high quality and quantity DNA from, as their leaves, shoots, and buds are particularly rich in carbohydrates, phenolic substances and secondary metabolites [ 1 , 2 , 3 ], contaminants that are difficult to remove during standard DNA isolation [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Commercial kits are relatively ineffective in extracting DNA from mature leaves of many species of interest [ 10 , 11 , 12 , 13 , 14 , 24 , 25 , 26 , 27 , 30 , 31 ] and require time-consuming and costly pre- and/or post-processing of samples. This may include the digestion of cell walls, isolation of intact protoplasts, enzymatic break down of sugars, isolation of nuclei, mitochondria or chloroplasts, the concentration of the extract, or the separation of DNA from contaminants [ 3 , 5 , 32 , 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Potassium acetate (PA) has been used to remove proteins during the isolations of DNA and RNA [2,15,24,25], for fixation of animal tissues in biological studies, as a food preservative [13], and to treat diabetic ketoacidosis via its ability to break down into bicarbonate [27]. Moreover, PA can help neutralize the human body from an acidotic state [27].…”
Section: Introductionmentioning
confidence: 99%